1997
DOI: 10.1111/j.1465-7287.1997.tb00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐profits Monopoly vs. Efficiency Debate: South African Evidence

Abstract: Using the new official measures of concentration, this study finds a strong and highly significant correlation between concentration and industry profitability for South African manufacturing industries. This correlation is consistent with both the monopoly hypothesis of the traditional structure-conduct-performance paradigm and Demsetz's efficiency hypothesis that concentration of industry reflects the dominance of superior low-cost firms. Copyright 1997 Western Economic Association International.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Conversely, firms within an unconcentrated industry will likely behave competitively, driving down profitability. Another argument is that concentration affects profitability through the large-share firms' ability to control prices (i.e., monopoly power) independently of their disposition towards collusion (Leach, 1997). There also exists a vast body of empirical studies, which has found a positive relationship between concentration and profits (e.g., Weiss, 1974;Martin, 1983;Imel and Helmberger, 1971).…”
Section: Industry Effects On Profitabilitymentioning
confidence: 99%
“…Conversely, firms within an unconcentrated industry will likely behave competitively, driving down profitability. Another argument is that concentration affects profitability through the large-share firms' ability to control prices (i.e., monopoly power) independently of their disposition towards collusion (Leach, 1997). There also exists a vast body of empirical studies, which has found a positive relationship between concentration and profits (e.g., Weiss, 1974;Martin, 1983;Imel and Helmberger, 1971).…”
Section: Industry Effects On Profitabilitymentioning
confidence: 99%
“…An important tenet in industrial organization, as explained by Leach (1997), is the concern that when an industry is highly concentrated, collusion among major players becomes easy, leading to monopoly pricing. Un-concentrated industries, on the other hand, are competitive, which promotes efficient pricing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The "first wave" of papers on markups in South African industry -such as Reekie (1984), Leach (1992Leach ( , 1997 and Fourie and Smith (2001) -were primarily concerned with the SCP-style markupsconcentration relationship discussed below, and often did not report markup summary statistics. These papers calculated manufacturing accounting markups (discussed in Section 3.2).…”
Section: Markupsmentioning
confidence: 99%
“…These papers calculated manufacturing accounting markups (discussed in Section 3.2). Where these were reported, markups were usually relatively low -in the range of 15% to 30% (Reekie 1984;Leach 1997). However the "second wave" of South African evidence on markups -mainly associated with Johannes Fedderke and coauthors -has in general estimated markups using Roeger's (1995) method of the "nominal Solow Residual" (NSR), based on Hall's (1988) relation between the residual and the mark-up.…”
Section: Markupsmentioning
confidence: 99%